UPDATE paling fresh ...!!! Detik-detik belajar habis-habisan UN SMA/MA IPS 2015 /Adi Prasetia...[et.al]; penyunting Dita Anggraini - Adi Prasetia...[et.al]; Dita Anggarini (Cakrawala, 2014)
vii, 472 hlm : ilus.; 28 cm